2016
DOI: 10.1137/15m1042632
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation of Lunisolar Secular Resonances for Space Debris Orbits

Abstract: Using bifurcation theory, we study the secular resonances induced by the Sun and Moon on space debris orbits around the Earth. In particular, we concentrate on a special class of secular resonances, which depend only on the debris' orbital inclination. This class is typically subdivided into three distinct types of secular resonances: those occurring at the critical inclination, those corresponding to polar orbits, and a third type resulting from a linear combination of the rates of variation of the argument o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Increasing A/m and adding drag to the model basically 'shift' the curves to higher q 0 . However, the dependence on A/m and drag is much smaller at high inclinations, where the main dynamical mechanism responsible for reentry is the overlapping of lunisolar resonances, as found in recent studies (see Celletti et al 2016;Gkolias et al 2016).…”
Section: Discussionsupporting
confidence: 59%
“…Increasing A/m and adding drag to the model basically 'shift' the curves to higher q 0 . However, the dependence on A/m and drag is much smaller at high inclinations, where the main dynamical mechanism responsible for reentry is the overlapping of lunisolar resonances, as found in recent studies (see Celletti et al 2016;Gkolias et al 2016).…”
Section: Discussionsupporting
confidence: 59%
“…The canonically conjugated vector of angles is classically denoted (ℓ, g, h). Omitting details that might be found in Celletti et al [9,11], the disturbing function of the Sun's attraction, R ⊙ , reads as…”
Section: Derivation Of the Hamiltonian Modelmentioning
confidence: 99%
“…This procedure involved the introduction of resonant coordinates through canonical transformations T k ∈ SL(3, Q) leading to an intuitive physical interpretation of Chirikov's overlap as a driver of chaos. However, since the work of Celletti et al [9], it has been observed that such a reduction does not always capture the features of the dynamics. In order to get a more refined and precise view of the extent of chaos, a superior way is instead to look at the destruction of KAM curves, e.g., using fast dynamical indicators.…”
Section: Secular Lunisolar Resonancesmentioning
confidence: 99%
See 2 more Smart Citations